Polycystins, focal adhesions and extracellular matrix interactions - Drummond, Iain A. (2011)
Polycystic Kidney disease is the most common heritable disease in humans. In addition to epithelial cysts in the kidney, liver and pancreas, patients with Autosomal Dominant Polycystic Kidney Disease (ADPKD) also suffer from abdominal hernia, intracranial aneurysm, gastrointestinal cysts, and cardiac valvular defects; conditions often associated with altered extracellular matrix production or integrity. Despite more than a decade of work on the principal ADPKD genes, PKD1 and PKD2, questions remain about the basis of cystic disease and the role of extracellular matrix in ADPKD pathology. This review explores the links between Polycystins, focal adhesions, and extracellular matrix gene expression. These relationships suggest roles for Polycystins in cell-matrix mechanosensory signaling that control matrix production and morphogenesis.